Heart rate responses to a kickboxing training session - Beuttemmüller, L. J.; Luz, S. R. d.; Bueno, G. C.; Eloa Jacques , E. J.; Milanez, V. F.; Moraes, S. M. F. d.; Pedro, R. E. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Physical inactivity and sedentary lifestyle have been growing exponentially and forms of physical exercise are needed. Previous research showed that others martial arts make improvement in physical fitness. Kickboxing appears as an alternative of exercise that may lead to increases in fitness, however no studies have described the intensity of a kickboxing training session (TS). Therefore, the aim of this study was the knowledge about the intensity distribution during a kickboxing training sessions.